Dampak Pengembangan Desa Wisata Terhadap Perekonomian, Sosial Masyarakat Desa Wonomerto Kecamatan Wonosalam Kabupaten Jombang - Dwi Wahyuni; Lina Susilowati (STIE PGRI Dewantara Jombang, 2020)
Referring to the Law No. 6 of 2014 concerning Villages, currently in the village of Wonomerto development activities are being carried out in tourist villages. The results of the development of a tourist village in Wonomerto which is currently being managed by the community are Sumber Biru and Batu Pelangi. The objectives of the research are (1) to describe the dynamics of local community participation in the development of tourism villages in Wonomerto Village, (2) to explain the impact of the development of tourism villages on the economy, social, culture, and environment of Wonomerto Village. The method used in this research is to use a qualitative phenomenological approach. As for analyzing data using three stages, namely (1) data reduction; (2) data exposure (data display); (3) drawing conclusions and verification (conclusion drawing / verifying).The result showed that the dynamics of Wonomerto community participation in the development of this tourist village took the form of self-mobilization. The impact that affect the life of the Wonomerto community from the development activities of this tourism village are (1) the opening of new tourist sites namely Sumber Biru and Batu Pelangi which can add new tourist destinations in Jombang District; (2) an increase in the family economy, especially in coffee farmers (rising coffee prices Exelca), breeders (additional income from the sale of organic fertilizer), and housewives (additional income from selling results in the tourist location Sumber Biru and Batu Pelangi); (3) the preservation of old traditions that had been lost or disappeared for decades namely the “Kenduren Kopi” tradition in Wonomerto; (4) people become more concerned about the environment especially rivers by not dumping livestock manure into the river anymore but the waste is processed into organic fertilizer; (5) people are more creative in making use of vacant houses by planting herbs and fruit.